2014
DOI: 10.1186/1743-8977-11-21
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicity of silver nanoparticles in an intravenous 28-day repeated-dose toxicity study in rats

Abstract: BackgroundNanosilver is used in a variety of medical and consumer products because of its antibacterial activity. This wide application results in an increased human exposure. Knowledge on the systemic toxicity of nanosilver is, however, relatively scarce. In a previous study, the systemic toxicity of 20 nm silver nanoparticles (Ag-NP) was studied in a 28-day repeated-dose toxicity study in rats. Ag-NP were intravenously administered with a maximum dose of 6 mg/kg body weight (bw)/day. Several immune parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 22 publications
2
45
0
Order By: Relevance
“…AgNPs are known for their antimicrobial properties [26,27]. On the other hand, some studies have associated potential harmful effects to these NPs [28,29]. In this study, evaluation of the physico-chemical characteristics of AgNP 15 when dispersed in different physiological solutions, such as RPMI culture medium + autologous serum or HBSS buffer alone demonstrated that the NPs remain relatively stable under these conditions.…”
Section: Discussionmentioning
confidence: 73%
“…AgNPs are known for their antimicrobial properties [26,27]. On the other hand, some studies have associated potential harmful effects to these NPs [28,29]. In this study, evaluation of the physico-chemical characteristics of AgNP 15 when dispersed in different physiological solutions, such as RPMI culture medium + autologous serum or HBSS buffer alone demonstrated that the NPs remain relatively stable under these conditions.…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, increases in spleen weight and spleen cell number are observed, which are not entirely consistent with the reduced KLH-specific IgG production. (Vandebriel et al, 2014) In line with these observations, the 28 day oral administration of 0.25, 2.5 or 25 ppm Ag nanoparticles has been shown to modulate the proliferative activity and cytokine production of murine splenocytes. Administration of 0.25 ppm Ag nanoparticles results in a significant inhibition of T cell proliferation and an augmentation of pro-inflammatory cytokine production by unstimulated and LPSstimulated cells.…”
Section: Silver Nanoparticlesmentioning
confidence: 64%
“…Also, AgNPs have been reported to cross the blood-brain barrier in rats and induce neuronal degeneration and necrosis through accumulation in the brain over a long period of time [82]. Additionally, Vandebriel et al and de Jong et al found that intravenous administration of both 20 and 100 nm AgNPs in a 28-day repeated-dose toxicity study in SD rats induces suppression of the functional immune system [83,84]. In the area of development, a study reported that AgNPs less than 12 nm in size affected early development of fish embryos, caused chromosomal aberrations and DNA damage, and induced proliferation arrest in cell lines of zebrafish indicating that AgNPs must be investigated for their potential teratogenic effects in humans [85].…”
Section: Toxicity Of Agnpsmentioning
confidence: 99%